Time-restricted feeding reduces monocyte production by controlling hematopoietic stem and progenitor cells in the bone marrow during obesity - Kim, Yelim; Lee, Youngyoon; Lee, Mi Nam; Nah, Jiyeon; Yun, Narae; Wu, Dayong; Pae, Munkyong (Frontiers in Immunology, 2022)
Time-restricted feeding (TRF) has emerged as a promising dietary approach in improving metabolic parameters associated with obesity, but its effect on immune cells under obesogenic condition is poorly understood. We conducted this study to determine whether TRF exerts its therapeutic benefit over obesity-induced myeloid cell production by analyzing hematopoietic stem and progenitor cells in bone marrow (BM) and immune cell profile in circulation. Male C57BL/6 mice were fed a low-fat diet (LFD) or high-fat diet (HFD) ad libitum for 6 weeks and later a subgroup of HFD mice was switched to a daily 10 h-TRF schedule for another 6 weeks. Mice on HFD ad libitum for 12 weeks had prominent monocytosis and neutrophilia, associated with expansion of BM myeloid progenitors, such as multipotent progenitors, pre-granulocyte/macrophage progenitors, and granulocyte/macrophage progenitors. TRF intervention in overweight and obese mice diminished these changes to a level similar to those seen in mice fed LFD. While having no effect on BM progenitor cell proliferation, TRF reduced expression of Cebpa, a transcription factor required for myeloid differentiation. These results indicate that TRF intervention may help maintain immune cell homeostasis in BM and circulation during obesity, which may in part contribute to health benefits associated with TRF.